The binding vine - Deshpande, Shashi; Sarker, Sonita (New York : The Feminist Press at CUNY, 2001)
From one of India's most acclaimed writers--a radiant novel, now available in paperback.
Keywords: Female friendship -- Fiction; Infants -- Death -- Fiction; Mother and child -- Fiction; English literature